Evidence for a new Z-type left-handed DNA helix: properties of Z(WC)-DNA. - Ansevin, A T (1990)
The structure of Z-DNA, currently accepted as a model for all left-handed DNAs, fails to provide convincing explanations for at least four well established properties of left-handed DNA polymers in solution. However, the major discrepancies between theory and experiment are resolved by the structure presently proposed for Z[WC]-DNA, a new left-handed, zig-zag double helix with Watson-Crick-type backbone directions. Structural features of Z[WC]-DNA include the presence of an additional H-bond between each guanine N2-amino group and an adjacent phosphate oxygen, the capacity to form four-stranded, base-matched complexes that should readily precipitate from solution, and backbone progressions that are the same as B-DNA (opposite to Z-DNA). However, since Z[WC]-DNA and Z-DNA have many parameters in common, they could be difficult to distinguish in a majority of existing experiments. In view of the close relationship of the new helix to B-DNA, which allows a relatively unhindered right-to-left transition in handedness, Z[WC]-DNA is theorized to be the left-handed structure preferentially generated in vivo by the torque available in naturally occurring DNA supercoils.